2000
DOI: 10.1038/35001586
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the conformational wave of acetylcholine receptor channel gating

Abstract: Allosteric transitions allow fast regulation of protein function in living systems. Even though the end points of such conformational changes are known for many proteins, the characteristics of the paths connecting these states remain largely unexplored. Rate-equilibrium linear free-energy relationships (LFERs) provide information about such pathways by relating changes in the free energy of the transition state to those of the ground states upon systematic perturbation of the system. Here we present an LFER a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
338
5

Year Published

2004
2004
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 312 publications
(367 citation statements)
references
References 29 publications
16
338
5
Order By: Relevance
“…Although the precise location of the gate has been equivocal (8,13), the 4-Å density map of the nAChR (6) and recent MTS studies with glycine, ␥-aminobutyric acid, type A, and 5-HT 3 receptors implicate movement between the 6Ј and 13Ј positions (7,9,10,57). In support of this, linear free energy relationship analysis of mutant nAChRs suggested that the cytoplasmic side of M2 moves last upon activation after a wave of energy moving from the site of ligand binding down toward the cytoplasmic selectivity filter (61,62). Although linear free energy relationship analysis does not reveal information concerning the extent of movement, these studies suggest that for residues below the 11Ј site, the structure of the transition state (the highest energy state the receptor attains during gating) closely resembles that of the closed state.…”
Section: Discussionmentioning
confidence: 60%
“…Although the precise location of the gate has been equivocal (8,13), the 4-Å density map of the nAChR (6) and recent MTS studies with glycine, ␥-aminobutyric acid, type A, and 5-HT 3 receptors implicate movement between the 6Ј and 13Ј positions (7,9,10,57). In support of this, linear free energy relationship analysis of mutant nAChRs suggested that the cytoplasmic side of M2 moves last upon activation after a wave of energy moving from the site of ligand binding down toward the cytoplasmic selectivity filter (61,62). Although linear free energy relationship analysis does not reveal information concerning the extent of movement, these studies suggest that for residues below the 11Ј site, the structure of the transition state (the highest energy state the receptor attains during gating) closely resembles that of the closed state.…”
Section: Discussionmentioning
confidence: 60%
“…It has been studied with single channel analysis and linear free energy relationship of gating rate constants by different mutations at each position. The results have suggested that there is a gradient change in the Φ slope factor of the linear free energy relationship, derived from the channel gating constants (opening and closing rates) of the mutations at each position, along the activation pathway [45] . Further analysis revealed that the gradient change in allosteric activation network is not continuous.…”
Section: Activation Mechanismmentioning
confidence: 99%
“…If there is a speed limit to channel-opening, then adding a background mutation, that by itself increases the opening rate constant, to a construct that is already operating at the speed limit should have no effect. We tested this prediction by measuring b in AChRs having the mutation ␣S269I, which is in the extracellular linker and which by itself is predicted to increase the ACh-induced opening rate Ϸ25-fold and to slow the closing rate constant Ϸ4-fold (8). Burst durations were measured in constructs having only this mutation as well as in doublesubstitution constructs that carried a second mutation (␣D97A) that alone increased the opening rate constant 130-fold (Table 1) ⌽ Values.…”
Section: [4]mentioning
confidence: 99%
“…For a series of point mutations, the slope (⌽) of a log-log plot of the opening rate constant vs. the equilibrium constant is an index of the extent of progress of the perturbed site at the transition state of the reaction. In fully liganded AChRs, there is, to a first approximation, a longitudinal gradient in ⌽-values, with residues near the transmitter binding sites being open-like (⌽ Ϸ 1) and some of those in the transmembrane region being closed-like (⌽ Ϸ 0) at the transition state (8,9). These results have been interpreted as indicating that gating occurs as a reversible solitary conformational ''wave'' that links structural changes in the affinity of the binding sites with structural changes that determine ionic conductance.…”
mentioning
confidence: 99%